CONSTRUCTED CONSCIOUSNESS AND THE LEADERSHIP PARADOX IN INDONESIA’S RELIGIOUS MODERATION MOVEMENT - Nasution, Hasan Bakti; Jailani, Muhammad; Ismahani, Siti (State Islamic University North Sumatra, 2025)
This study investigates how collective consciousness is framed by religious moderation activists and how false consciousness emerges within Indonesia’s religious moderation movement. Using a qualitative comparative approach, data were collected through in-depth interviews, focus group discussions, and secondary sources in North Sumatra and North Sulawesi. Findings reveal that collective consciousness is framed through political discourse, theological narratives, cultural references, and memories of conflict and injustice. In North Sumatra, theological framing is dominant, producing a fragmented harmony that is institutionally grounded yet exclusive. By contrast, North Sulawesi demonstrates performative harmony, emphasizing universal slogans while denying latent conflicts. Despite these contextual differences, both regions sustain harmony through forms of false consciousness—maintaining peace by avoiding open confrontation rather than fostering genuine negotiation.